CLASSIFICATION OF L2 WRITING PROCESS AND WRITING STRATEGIES - Imelda Hermilinda Abas; Noor Hashima Abd Aziz (Proceedings of The ICECRS, 2016)
English for second language writing has developed greatly, from product oriented approach to process oriented approach. This implies that the focus of L2 writing has shifted from the final product of writing to the process of writing. Because of its own rules and conventions, writing skill is considered difficult to learn in a short period of time. Although it is a difficult skill, writing is essential for second language learners’ academic success. Second language researchers are still trying to find satisfactory answers to the how and why of the teaching of writing process to second language learners. More studies are needed to shed light on second language writing process area. This paper discusses briefly the writing process and the writing strategies employed by a few EFL proficient student writers in writing. It is found that the writing process stages employedin this study were prewriting, planning, drafting, pausing and reading, revising and editing which occurred non-linear and recursive. The writing strategies identified in the writing process stages were relating the topic to past knowledge and experience, taking the readers into consideration, talk-write, freewriting, outlining, listing, seeking help, using online materials, focusing on the mechanics of writing, and text organization. However, what works successfully for some students may not work well for others, and what functions well for one assignment may not be compatible for another.